Central African Republic : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that the Central African Republic's period since 2000 has been marked by poor economic performance, owing in large part to military disturbances, but also to weak administration and poor program implementation. The conflict that ended in March 2003 shattered the Central African Republic's economy. Real GDP contracted by 7 percent in 2003, with the formal sector of the economy in a particularly dire state. The deficit in the overall budget balance including grants widened by about 2 percent of GDP in 2003.